PENGUKURAN EFEKTIFITAS PENGIKLANAN LINGKUNGAN MELALUI IKLAN TELEVISI (PENDEKATAN MODEL AIDA) - Adawiyah Sis, Atika Robiatun; ,, Albari (KINERJA, 2015)
Advertising can no longer be simply regarded as one type of marketing communications but it should be packaged as one seed strategy in the context of the overall marketing strategy. In the development of theterm advertising or advertising green environment, it is stated as a strategy that tries to create a culture and identity of the consumers who care about the environment. This study measures the environmental importanceof advertising that is linked to the purpose of advertising itself based on AIDA approach. The study is conducted with the involvement of consumers who have seen a particular brand advertising of Drinking Water in Yogyakarta. 166 respondents are selected using convenience sampling technique. While the data obtained through the questionnaire are analyzed by using a structural equation modelling (SEM) and the data processing program AMOS 20.0, after going through two stages of testing the validity and reliability. The results show that advertising environment is positive and gives significant contribution to the AIDA in the case of television advertising. While the influence of the greatest predictive total advertising environment happens to consumer desire to buy. It is also concluded that the variables of attention, interest, and desire to serve as a mediator variable influence of environment on the advertising of interest, desire, and action of consumers to buy.Keywords: environmental advertising, attention, interest, desire, action